2011
DOI: 10.1183/09031936.00151110
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, insulin resistance and sleepiness in real-life obstructive sleep apnoea

Abstract: The metabolic syndrome shows a variable prevalence in obstructive sleep apnoea (OSA), and its association with insulin resistance or excessive daytime sleepiness in OSA is unclear. This study assessed the following in consecutive patients with newly diagnosed OSA: 1) the prevalence of metabolic syndrome; and 2) its association with insulin resistance and daytime sleepiness.Metabolic syndrome (National Cholesterol Education Program Adult Treatment Panel (NCEP-ATP) III criteria), insulin resistance (Homeostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 43 publications
5
91
1
5
Order By: Relevance
“…The number of MetS criteria is defined as the metabolic index and can be used as an indicator of severity of metabolic abnormalities. Patients with severe OSA showed a significantly higher metabolic index compared to patients with mild-to-moderate OSA [45], and this finding has been also confirmed in patients primarily identified for the presence of MetS [46] or morbid obesity [47]. An independent role of OSA on metabolic abnormalities is not strongly supported by randomised controlled trials rigorously testing the effect of CPAP on metabolism in OSA patients.…”
Section: Osa Visceral Fat and The Metabolic Syndromementioning
confidence: 78%
See 1 more Smart Citation
“…The number of MetS criteria is defined as the metabolic index and can be used as an indicator of severity of metabolic abnormalities. Patients with severe OSA showed a significantly higher metabolic index compared to patients with mild-to-moderate OSA [45], and this finding has been also confirmed in patients primarily identified for the presence of MetS [46] or morbid obesity [47]. An independent role of OSA on metabolic abnormalities is not strongly supported by randomised controlled trials rigorously testing the effect of CPAP on metabolism in OSA patients.…”
Section: Osa Visceral Fat and The Metabolic Syndromementioning
confidence: 78%
“…3). MetS is diagnosed in clinical practice by the NCEP-ATP (National Cholesterol Education ProgrammeAdult Treatment Panel) III criteria, which require the presence of three out of five criteria [36][37][38][39][40][41][42][43][44][45]. The number of MetS criteria is defined as the metabolic index and can be used as an indicator of severity of metabolic abnormalities.…”
Section: Osa Visceral Fat and The Metabolic Syndromementioning
confidence: 99%
“…Its prevalence in obstructive sleep apnea patients has been reported to reach the levels of 47% [37]. Early reports suggested that resistin is associated with obesity and insulin resistance in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, it has been estimated that at least half of patients with OSA fulfil the criteria for the metabolic syndrome [5]. Furthermore, the prevalence of metabolic syndrome increases with OSA severity [5,6]. An independent dose-response relationship has been demonstrated between OSA severity and the features of metabolic syndrome, including visceral adiposity [7], hypertension [8], metabolic dyslipidaemia [6] and impaired glucose metabolism [9,10].…”
mentioning
confidence: 99%
“…Besides OSA-related variables, comorbid conditions including hypertension and metabolic dysfunction play an important role in the development of cardiovascular diseases in OSA patients [4]. In the clinical setting, it has been estimated that at least half of patients with OSA fulfil the criteria for the metabolic syndrome [5]. Furthermore, the prevalence of metabolic syndrome increases with OSA severity [5,6].…”
mentioning
confidence: 99%